The associations of supervisor support and work overload with burnout and depression: a cross‐sectional study in two nursing settings. (4th March 2016) - Weigl, Matthias; Stab, Nicole; Herms, Isabel; Angerer, Peter; Hacker, Winfried; Glaser, Jürgen
Abstract: Aims: To investigate the moderating effects of work overload and supervisor support on the emotional exhaustion–depressive state relationship. Background: Burnout and depression are prevalent in human service professionals and have a detrimental impact on clients. Work overload and supervisor support are two key job demands and job resources, whose role and interplay for the development and maintenance of burnout and depression are not fully understood yet. Design: Two consecutive cross‐sectional surveys: survey 1 investigated 111 hospital nursing professionals and survey 2 examined 202 day care professionals. Data collection was completed in 2010. Results: After controlling for general well‐being and sociodemographic characteristics, nurses' emotional exhaustion was associated with increased depressive state in both samples. We found a meaningful three‐way interaction: our results show consistently that the relationship between emotional exhaustion and depressive state was strongest for nurses with high work overload and low supervisor support. Additionally, nurses with low work overload and low supervisor support were also found to have stronger associations between emotional exhaustion and depressive state. Conclusion: The findings indicate that nurses' reported supervisor support exerts its buffering effect on the burnout‐depression link differentially and serves as an important resource for nurses dealing with high self‐reported work stress.